2012
DOI: 10.1111/j.1471-0528.2012.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of recurrent anal sphincter ruptures: a population‐based cohort study

Abstract: Objective To determine the incidence and risk factors of recurrent anal sphincter rupture (ASR).Design Population-based retrospective cohort study.Setting Data were taken from the National Medical Birth Registry, Denmark.Population Patients with a first and a second vaginal delivery in the time period 1997-2010.Methods Univariate analysis and multivariate logistic regression were used to determine risk factors of recurrent ASR.Main outcome measures The incidence of recurrent ASR and odds ratios for possible ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(79 citation statements)
references
References 17 publications
7
70
2
Order By: Relevance
“…This is a relevant concern given that a repeated injury is known to occur in seven of 10 women with a subsequent delivery. [6] An interesting finding in our study was that the women made a distinction between the experience of bearing a child and giving birth, being pregnant for 40 weeks was considered a positive experience while the thought of the actual birth was frightening.…”
Section: Inability To Function Sexuallymentioning
confidence: 66%
See 3 more Smart Citations
“…This is a relevant concern given that a repeated injury is known to occur in seven of 10 women with a subsequent delivery. [6] An interesting finding in our study was that the women made a distinction between the experience of bearing a child and giving birth, being pregnant for 40 weeks was considered a positive experience while the thought of the actual birth was frightening.…”
Section: Inability To Function Sexuallymentioning
confidence: 66%
“…Risk factors for OASR are: maternal age (> 35 years), [1,2] primiparity, [1,3,4] prolonged second stage of labor (i.e. > 2 hours), [1,5] oxytocin argumentation, instrumental delivery (both mid release vacuum extraction [VE] and outlet VE), [1] VE without episiotomy, [6] and birth weight > 4,000 grams. [1,5] The risk of an OASR with a subsequent birth is 7.1%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In women who suffered OASIS at first birth, the incidence of a repeat OASIS has been shown to be 8.4% in hospital-based studies 2 and 7.2% in population-based studies 3 in the United Kingdom. In other countries, the rate of repeat OASIS in hospital-based and population-based studies has been reported to range widely from 2.0 to 7.2% 4,5 and from 5.6 to 7.1% 6,7 , respectively. Even though there are well defined risk factors for the occurrence of OASIS, such as nulliparity and instrument assistance at birth, the combination of these risk factors in different scoring systems does not allow the accurate prediction of OASIS 8 .…”
mentioning
confidence: 99%